Notes on Paepalanthus (Eriocaulaceae) from central Brazil and Paraguay - Trovó, Marcelo; Echternacht, Lívia (Phytotaxa, 2023)
Paepalanthus balansae, P. lundii, and P. scholiophyllus are morphologically related species growing in swampy areas of central South America, and are frequently misidentified in collections worldwide. We discuss here new and relevant morphological data to elucidate the circumscription of these species. Paepalanthus balansae is maintained as a distinct species following its current circumscription, while the wide morphological variation of P. scholiophyllus is understood here within a broader P. lundii concept and treated as synonymous. We report herein the presence of short lateral branches covered by a few bracts and subtending a single or a few inflorescences for the first time in P. lundii and P. balansae. This character, along with floral details and the scarce molecular data available, reinforce that these species are closely related to Actinocephalus. We also provide nomenclatural adjustments for the types and infrageneric names related to these taxa, along with a distribution map and images.